2020
DOI: 10.1007/s11596-020-2229-6
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolin Mediates LPS-induced Expression of Inflammatory Mediators and Activation of Signaling Pathways

Abstract: In this study, we investigated the effects of nucleolin on lipopolysaccharide (LPS)induced activation of MAPK and NF-KappaB (NF-κB) signaling pathways and secretion of TNF-α, IL-1β and HMGB1 in THP-1 monocytes. Immunofluorescence assay and Western blotting were used to identify the nucleolin expression in cell membrane, cytoplasm and nucleus of THP-1 monocytes. Inactivation of nucleolin was induced by neutralizing antibody against nucleolin. THP-1 monocytes were pretreated with anti-nucleolin antibody for 1 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Accordingly, nucleolin knockdown inhibits GSK-3β phosphorylation and reduces β-catenin protein [50]. A recent study showed that anti-nucleolin neutralizing antibody inhibits NF-κB nuclear translocation and inflammatory gene expression induced by lipopolysaccharide, a TLR4 ligand [51]. These findings suggest that nucleolin antagonism by iSN04 inhibits GSK-3β phosphorylation, which leads to β-catenin degradation and NF-κB inactivation, eventually exerting an anti-inflammatory effect.…”
Section: Discussionmentioning
confidence: 95%
“…Accordingly, nucleolin knockdown inhibits GSK-3β phosphorylation and reduces β-catenin protein [50]. A recent study showed that anti-nucleolin neutralizing antibody inhibits NF-κB nuclear translocation and inflammatory gene expression induced by lipopolysaccharide, a TLR4 ligand [51]. These findings suggest that nucleolin antagonism by iSN04 inhibits GSK-3β phosphorylation, which leads to β-catenin degradation and NF-κB inactivation, eventually exerting an anti-inflammatory effect.…”
Section: Discussionmentioning
confidence: 95%
“…Although there are clinical reports of acute neurological complications associated with RSV, the adverse effects of such complications have often been previously underestimated. In recent years, with the widespread reports of RSV‐related encephalopathy, an increasing number of scholars have realized that RSV‐related neurological symptoms are important clinical manifestations, and the possibility of RSV infection should be considered when children present with acute neurological symptoms 36 . The pathogenesis of RSV‐related encephalopathy may vary, and our previous studies have shown that TLR4 and NCL co‐mediate the infection of neurons by the virus, but the specific mechanism remains to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…The above studies suggest that the GAR domain of NCL may be an important receptor domain of RSV‐infected nerve cells. The M protein is a non‐glycosylated structural protein lining the inner leaflet of the viral envelope that binds to the cytoplasmic structural domains of F proteins 36 . Here, we examined M protein mRNA expression to reflect the effects of TIR and GAR on RSV replication.…”
Section: Discussionmentioning
confidence: 99%
“…The NF-κB and MAPK pathways are essential in regulating the production of inflammatory cytokines in activated macrophages such as TNF-α, IL-1β, and IL-6. TNF-α participates in various processes such as cell survival, apoptosis, and necrosis, by stimulating TNF receptors and related pathways, such as NF-κB and MAPKs [ 33 ]. The LPS-induced pattern of macrophage activation leads to high production of inflammatory mediators, such as TNF-α, IL-1β, and IL-6.…”
Section: Discussionmentioning
confidence: 99%